Phosphorus accumulation in soils and nitrate contamination in underground water under export-oriented asparagus farming in Nong Ngu Lauem village, Nakhon Pathom province, Thailand - Patcharaporn Phupaibul; Chatuporn Chitbuntanorm; Nanthana Chinoim; Pornthiwa Kangyawongha; Toru Matoh (My University, 2004)
Abstract Asparagus fields in Nong Ngu Lauem village, Nakhon Pathom province, Thailand, were surveyed for the cultural practices adopted, yield, fertilizer use, nutrient accumulation in soils, and nitrate-nitrogen concentration of the underground water. In this village, asparagus is being cultivated under contract farming with a Japanese agribusiness company and 60% of the product is exported to Japan. Average application rates of nitrogen- and phosphorus-fertilizers were 840 kg N and 286 kg P ha−1 year−1, and less than 5% of the applied elements was recovered in the harvested products. Phosphorus accumulated in the surface 20 cm soil significantly, unlike N determined by the Kjeldahl method. Higher concentration of nitrate-nitrogen was detected down to 1-m depth in the asparagus fields compared with the adjacent sugarcane fields. Underground water samples were taken from 15 wells of the village and their content of nitrate-nitrogen was determined once a month during a period of 18 months. Nitrate-nitrogen was distributed unevenly among the wells, and no periodic peaks in the concentrations were detected. The highest value of 39 g nitrate-nitrogen m−3 was recorded.
Keywords: Asparagus; Irrigation Practices and Water Management